If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(1+7x)6(7x)=36
We move all terms to the left:
(1+7x)6(7x)-(36)=0
We add all the numbers together, and all the variables
(7x+1)67x-36=0
We multiply parentheses
469x^2+67x-36=0
a = 469; b = 67; c = -36;
Δ = b2-4ac
Δ = 672-4·469·(-36)
Δ = 72025
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{72025}=\sqrt{25*2881}=\sqrt{25}*\sqrt{2881}=5\sqrt{2881}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(67)-5\sqrt{2881}}{2*469}=\frac{-67-5\sqrt{2881}}{938} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(67)+5\sqrt{2881}}{2*469}=\frac{-67+5\sqrt{2881}}{938} $
| -18=2k | | 100-4x=68 | | -78=-2(4+7a) | | 6x2=30x−18 | | 209.58=6(0.09m+25.70+0.10(25.70)) | | -3w-10w=-28 | | 3+2s=9s= | | 9x-6-5=45 | | 11h-8h=9 | | 1/3(9x-6)+5x=30 | | 180+(-20x)=360 | | A=3x-6 | | ?x2=676 | | 15=y12 | | -(16+4x)=18 | | 11+2p=3 | | 4x^2-4x-55=0 | | 5x-4-4=46 | | -12=r/6 | | -2/5x-6=4 | | (5x+6/2)=-4x+15 | | |u|+12=21 | | 8=-4+s | | ∣-3x−45∣=∣12x∣ | | t/8-4=5 | | k2+10=14 | | d=32*6 | | k2+ 10=14 | | z/6−2=2 | | -5=-3+-2g | | 12v-6=5 | | -5v-27=4(v-9) |